2006
DOI: 10.1021/jp062184v
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Successive Steps of Deprotonation of l- Phosphoserine through 13C and 31P Chemical Shielding Tensor Fingerprints

Abstract: The effects of deprotonation on the (13)C and (31)P chemical shielding tensors of L-O-phosphoserine are revealed by using solid-state NMR spectroscopy and ab initio calculations. The characteristic changes in some principal elements of the (13)C and (31)P chemical shift tensors have been detected during successive steps of deprotonation of carboxyl, phosphate, and amide functional groups. The calculations carried out in a polarizable continuum taking into account the effects of the surroundings have shown thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 33 publications
(55 reference statements)
5
28
3
Order By: Relevance
“…The structure refinements were evaluated further by 1 H and 13 C chemical shifts computed by the gauge including projector augmented wave (GIPAW) approach. 43 48 Our NMR results are contrasted with the comparatively sparse previous solid-state NMR reports on Pser that mainly focused on the (an)isotropic 31 P and 13 C chemical-shift parameters, 25 , 27 , 35 , 49 51 whereas most of the NMR parameters for CaPser are presented herein for the first time. We also discuss the 31 P NMR signatures of the phosphate groups of Pser and CaPser in relation to their proposed capabilities of monitoring the very initial bone-mineral formation events.…”
Section: Introductioncontrasting
confidence: 97%
“…The structure refinements were evaluated further by 1 H and 13 C chemical shifts computed by the gauge including projector augmented wave (GIPAW) approach. 43 48 Our NMR results are contrasted with the comparatively sparse previous solid-state NMR reports on Pser that mainly focused on the (an)isotropic 31 P and 13 C chemical-shift parameters, 25 , 27 , 35 , 49 51 whereas most of the NMR parameters for CaPser are presented herein for the first time. We also discuss the 31 P NMR signatures of the phosphate groups of Pser and CaPser in relation to their proposed capabilities of monitoring the very initial bone-mineral formation events.…”
Section: Introductioncontrasting
confidence: 97%
“…5,20 In this case, the average distance between the corresponding protein protons (from R-COOH or R-NH3 + or R-NH2) and the inorganic 31 P is ~3.4-3.1 Å, 5,20 which corresponds quite well to the proton chemical shift observed in the current work (~12 to 15 ppm). 16 We note that this distance is significantly greater than the average distance between the Hβ of serine and its phosphorous atom. As a result, these labile protons must be roughly two times as abundant as the Hβ in serine.…”
Section: Proton Proton Protonmentioning
confidence: 79%
“…This small change in the spectrum is attributed to a small increase in the concentration of positively charged ions, such as calcium, in the vicinity of the phosphorous in serine. 16 Indeed, the latter authors reported that an increase of the σ33 tensor indicates a slight disruption of H-bonds of 31 PpSer, which is a consequence of the proximity of ionic species. The relative intensities in the CP experiment indicate a more significant change in the sample.…”
Section: Proton Proton Protonmentioning
confidence: 97%
“…This is consistent with trends observed by C. Gardiennet et al in which the phosphate on L-O-Phosphoserine is doubly ionized. 49 This point is exemplified when comparing the caddisfly spectra to the CSA pattern of protonated L-phosphoserine from Sigma Aldrich. The presence of cations near the phosphorus resonance can also affect the CSA pattern, 50 so de-protonated phosphoserine was prepared in the presence of calcium, magnesium and sodium cations.…”
Section: Resultsmentioning
confidence: 99%